6x+5x+3+7=6x+4+4x

Simple and best practice solution for 6x+5x+3+7=6x+4+4x equation. Check how easy it is, and learn it for the future. Our solution is simple, and easy to understand, so don`t hesitate to use it as a solution of your homework.

If it's not what You are looking for type in the equation solver your own equation and let us solve it.

Solution for 6x+5x+3+7=6x+4+4x equation:


Simplifying
6x + 5x + 3 + 7 = 6x + 4 + 4x

Reorder the terms:
3 + 7 + 6x + 5x = 6x + 4 + 4x

Combine like terms: 3 + 7 = 10
10 + 6x + 5x = 6x + 4 + 4x

Combine like terms: 6x + 5x = 11x
10 + 11x = 6x + 4 + 4x

Reorder the terms:
10 + 11x = 4 + 6x + 4x

Combine like terms: 6x + 4x = 10x
10 + 11x = 4 + 10x

Solving
10 + 11x = 4 + 10x

Solving for variable 'x'.

Move all terms containing x to the left, all other terms to the right.

Add '-10x' to each side of the equation.
10 + 11x + -10x = 4 + 10x + -10x

Combine like terms: 11x + -10x = 1x
10 + 1x = 4 + 10x + -10x

Combine like terms: 10x + -10x = 0
10 + 1x = 4 + 0
10 + 1x = 4

Add '-10' to each side of the equation.
10 + -10 + 1x = 4 + -10

Combine like terms: 10 + -10 = 0
0 + 1x = 4 + -10
1x = 4 + -10

Combine like terms: 4 + -10 = -6
1x = -6

Divide each side by '1'.
x = -6

Simplifying
x = -6

See similar equations:

| 7*x+9*x=52 | | 35x*4=0 | | 8(b+4)=40 | | 14x-(9x-7)=11+(-3+62) | | (3*x)+5=53 | | 2x(9-7x)=0 | | k*p=16 | | h*h+g*g=64 | | s+5=7 | | s*s-12s+12=0 | | 3+27x+15=5x+18+22x | | 0.75*18+0.25*x=17 | | 0.25x^2-5x=10 | | 4p+2q=28 | | 1+a=b-1 | | 8n-30=42 | | 4p+3q=26 | | (x+-2)(x+-2)=-25 | | 400=16t | | 12x^2+25x-7=0 | | 7m+7n= | | 2x+4x+3y= | | 79-4x=23x+19 | | (n-5)*7=35 | | (n-6)*4=40 | | -171x-9x=10x+19 | | 3x+x/2=15 | | 3a-4=0 | | 8x+3=x+38 | | x*2=8 | | 4x*5x=20 | | 4x+3x=12 |

Equations solver categories